1995
DOI: 10.1177/0145482x9508900509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Blind Learning Aptitude Test to Braille Reading Skills

Abstract: The purpose of the study reported here was to determine the validity of the Blind Learning Aptitude Test (BLAT). The findings revealed significant correlations between scores on the BLAT and braille oral reading speed, comprehension, age, grade, years of blindness, intelligence, and achievement. The relationship between the BLAT scores and comprehension was stronger than the relationship between BLAT scores and braille reading speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Standardized tests typically have normative data that are based on chil dren without disabilities and, hence, may not be representative of the ability or skill level of a child who is visually impaired. Educators have argued that the validity of standardized test scores is affected by atypical development in cognitive, sen sory, motor, and emotional development (Baker & Koenig, 1995;Swallow, 1981;Warren, 1984). Additional factors con founding test measures have included dif ferences in the degree of vision loss and visual function, efficiency, and stamina (U.S. Department of Education, 2001).…”
Section: Discussion About Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized tests typically have normative data that are based on chil dren without disabilities and, hence, may not be representative of the ability or skill level of a child who is visually impaired. Educators have argued that the validity of standardized test scores is affected by atypical development in cognitive, sen sory, motor, and emotional development (Baker & Koenig, 1995;Swallow, 1981;Warren, 1984). Additional factors con founding test measures have included dif ferences in the degree of vision loss and visual function, efficiency, and stamina (U.S. Department of Education, 2001).…”
Section: Discussion About Validitymentioning
confidence: 99%
“…Additional factors con founding test measures have included dif ferences in the degree of vision loss and visual function, efficiency, and stamina (U.S. Department of Education, 2001). Baker and Koenig (1995) emphasized the need for normative data on children who are blind or visually impaired, and stated that comparing the test results of sighted students with those of students who are visually impaired is inappropriate. Bolt and Thurlow (2004) concluded that if tests are going to be used to make high-stakes decisions, then educators must carefully examine the validity of these tests when accommodations and modifications are being made.…”
Section: Discussion About Validitymentioning
confidence: 99%
“…Although standardized instruments are acceptable tools when considering instruction and intervention leading to identification of LD with VI, educators need to use caution as standardized tests are usually norm-referenced and may not sufficiently describe abilities of students with VI, as the expectation of multidisciplinary teams is that most students do not have sensory impairments. Comparing scores of normally sighted students with those who are VI on standardized instruments may be inappropriate (Baker & Koenig, 1995;Hannan, 2007). Further, when administering informal screening assessments to students with or suspected of having VI, child study teams should consider the conditions under which the student takes the test that may affect the external validity of the assessment (Pressley, 2003).…”
Section: Universal Screeningmentioning
confidence: 99%
“…Assessment for instructional purposes is critical to the appropriate education of students with LD and VI. Although they may be useful for identification due to state policy constraints, the treatment validity of standardized measures likely is not as good as curriculum-based measures that are more directly skill-focused (Baker & Koenig, 1995;Hannan, 2007;Pressley, 2003;Reid, 1998). Alternatively, criterionreferenced measures will also provide more helpful information for planning instruction than standardized measures (Hannan, 2007).…”
Section: Progress Monitoringmentioning
confidence: 99%